COMPARATIVE ANALYSIS OF SHARIA AND CONVENTIONAL STOCK RESILIENCE TO GLOBAL UNCERTAINTY: EVIDENCE FROM ISSI AND IHSG DURING 2019–2025 - Indarta, Ahmad; Setiawan, Agus (STIE AMA Salatiga, 2025)
ABSTRACT : This study examines the comparative resilience of Islamic and conventional stock markets in Indonesia under global uncertainty. Using monthly data for the Indonesian Sharia Stock Index (ISSI) and the Jakarta Composite Index (IHSG) from February 2019 to July 2025, the GARCH-X model is employed to capture volatility clustering and the exogenous effects of uncertainty shocks. Global uncertainty is proxied by three major events: the COVID-19 pandemic, the Russia–Ukraine conflict, and the Trump-era trade tariffs. The results show that both indices are significantly affected by global shocks, with the VIX serving as a key driver of volatility. However, ISSI demonstrates greater resilience, reflected in lower volatility persistence and faster stabilization aftershocks. Trade-related protectionist measures and commodity price increases provide additional support to Sharia-compliant firms, while IHSG remains more sensitive to U.S. monetary policy and global capital flow volatility. These findings highlight the role of Islamic equities as a stabilizing component in emerging markets and a viable tool for portfolio diversification and risk management during periods of global turbulence.ABSTRAK : Penelitian ini mengkaji daya tahan komparatif pasar saham syariah dan konvensional di Indonesia terhadap ketidakpastian global. Data bulanan Indeks Saham Syariah Indonesia (ISSI) dan Indeks Harga Saham Gabungan (IHSG) periode Februari 2019–Juli 2025 dianalisis menggunakan model GARCH-X untuk menangkap volatility clustering serta pengaruh eksogen dari guncangan global. Ketidakpastian global diproksikan melalui tiga peristiwa utama, yaitu pandemi COVID-19, konflik Rusia–Ukraina, dan kebijakan tarif era Trump. Hasil penelitian menunjukkan bahwa kedua indeks signifikan dipengaruhi oleh guncangan global, dengan VIX sebagai pendorong utama volatilitas. Namun, ISSI terbukti lebih tangguh, ditunjukkan oleh persistensi volatilitas yang lebih rendah dan stabilisasi yang lebih cepat pascaguncangan. Kebijakan proteksionis berbasis perdagangan dan kenaikan harga komoditas memberikan dukungan tambahan bagi emiten syariah, sementara IHSG lebih sensitif terhadap kebijakan moneter Amerika Serikat dan volatilitas arus modal global. Temuan ini menegaskan peran saham syariah sebagai komponen penstabil di pasar negara berkembang sekaligus instrumen yang efektif untuk diversifikasi portofolio dan manajemen risiko pada periode ketidakpastian global.